Immunological aspects of melanoma - Muse, Ignacio; Priario, Julio C (Cirugía del Uruguay, 1974)
In a new perspective of neoplastic pathology, the rclationship of host-tumor is considered as a dynamic and mutually beneficial equilibrium. The immunological elements gain recognition as regards melanoma, it being worthy of mention the identification of specific tumor antigen, as well as the cellular and/or humoral response of the host to them. The possibilities of different forms of immunotherapy are mentioned as complementary treatment, emphasizing, however, the fact that this new method is still in experimental stage. Consequently, it is recommended that applications be made only on the basis of very specific conditions, and circumscribed to carefully chose patients, counting on adequate technical assistance and possibility of control and evaluation.